Hubungan Kadar Timbal Di Lingkungan Dengan Kadar Hemoglobin Nelayan Yang Menangkap Dan Mengkosumsi Ikan Di Wilayah Tambang Timah Di Desa Air Lintang Kabupaten Bangka Barat Provinsi Kepulauan Bangka Belitung Tahun 2017 - Zainudin; Amar Muntaha; Rismala Kesuma (IKEMAS: Jurnal Ilmu Kesehatan Masyarakat, 2018)
The development of world?s industry both in small, medium and large scales could not ignore the role of ISO (International Standard Organization) 14000 about standard of enviromental management system. Off shore mining started to begin since the decreasing of ground mining. The rest of tin mining (tailing) contained heavy metal of Pb, Cd, and Cr. This study examines the hemoglobin levels within fishermen?s blood who caught and consumed the fish at the sea  tin mining area of Tempilang District, West Bangka Regency, Bangka Belitung Islands province on january 22 to February 15 2017. The samples of this study were the forty eight fishermen of Air Lintang village who caught and consumed the fish at the sea tin mining area, with purposive random sampling. The data were collected by taking sample off is hermen?s blood and checking the hemoglobin?s levels off is hermen with measuring scale of 14 gr/dl which fulfilled the requirement, while under 15 gr/dl did not fulfill the requirement of hemoglobin?s level, also by observation and quistionaire. . This study used the guantitative method and cross sectional. Data analysis of this research using univariate, bivariate and multivariate. The result of this study shows 25 respondents whose hemoglobin?s levels? fulfill the requirements, while 23 others from subject of bivariate chi square?s result which were taken from respondents? characteristic ages (p Value 0.081), smoking habit (p Value 0.191), working day per year (0.248) fishing distance (p Value 0.021) then there was one result of multivariate regression logistic which influences fishermen?s hemoglobin level that is fishing distance?s value sig 0.025. The mean who catch the fish with the distance. mile hemoglobin level 13.07. The fishermen who catch the fish with the distance  1 to 2 miles hemoglobin level 14.27 gr/dl, while there was no effect on the other variable because the p Value.is more than value of ?=0.05. To the fishermen of Air Lintang village not to catch the fish less than 1 mile from sea tin mining because of the low of hemoglobin level for the fishermen who catch the fish less than 1 mile distance.